Low anterior resection syndrome (LARS) - Rajendra, S. (The Sri Lanka Journal of Surgery, 2019)
Patients develop a variety of bowel dysfunction following low or very low anterior resection for rectal cancer. These symptoms are known collectively as low anterior resection syndrome (LARS), and the extent to which it affects the quality of life of these patients can be assessed by the LARS score. Knowledge about anorectal functional anatomy is a prerequisite to understanding the aetio-pathology and clinical manifestation of LARS. Structural and functional impairment of the internal and external anal sphincter and the anal transition zone, loss of reservoir function of the rectum, increased colonic motility, proximal diversion, enteric nervous system remodelling and neuropathy of autonomic nerves in the pelvis are known to cause LARS.
Keywords: Neorectum; Aetio-pathology; QOL; LARS; Dyspareunia; Ileostomy